2020
DOI: 10.1590/0100-3984.2019.0063
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of retrospective application of the Vesical Imaging-Reporting and Data System: preliminary results

Abstract: Objective: To evaluate the retrospective accuracy of the Vesical Imaging-Reporting and Data System (VI-RADS) in detecting muscle invasion in bladder cancer. Materials and Methods: We investigated patients who underwent pelvic magnetic resonance imaging and were submitted to transurethral resection of a bladder tumor between 2015 and 2018. Thirty cases were reviewed by radiologists blinded to the final clinical stage. The VI-RADS score was applied and compared with the histopathological findings in the surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…After 161 duplicates were removed and the titles and abstracts of the 38 remaining articles were screened, 26 potential articles were obtained. Full‐text reviews were considered, and 20 studies met the inclusion criteria, 14–33 whereas the other six studies were excluded for the following reasons: original study involving VI‐RADS ( n = 2), non‐English language ( n = 1) and insufficient information provided ( n = 3). Ultimately, the 20 included studies that reported on 2725 patients with more than 2861 lesions provided the raw data of this meta‐analysis, as shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 161 duplicates were removed and the titles and abstracts of the 38 remaining articles were screened, 26 potential articles were obtained. Full‐text reviews were considered, and 20 studies met the inclusion criteria, 14–33 whereas the other six studies were excluded for the following reasons: original study involving VI‐RADS ( n = 2), non‐English language ( n = 1) and insufficient information provided ( n = 3). Ultimately, the 20 included studies that reported on 2725 patients with more than 2861 lesions provided the raw data of this meta‐analysis, as shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 12 studies used scanners that provided a magnet strength of 3 T, whereas eight used scanners with a magnet strength of 1.5 T or the combination of 1.5 and 3 T. The bladder was distended in all 20 studies using multiple methods, such as holding back urine, oral hydration, saline injection using a catheter or drugs that inhibit bladder contraction. MpMRI was carried out before TURBT in all cases except for one study, 26 in which 26.6% of patients underwent MRI after bladder biopsy or TURBT. Parameters differed among the included studies, and all studies met the requirement to obtain sufficient information that followed the recommendations of the VI‐RADS guideline 10 .…”
Section: Resultsmentioning
confidence: 99%
“…Retrospective studies From our review, 12 retrospective studies performed between 2019 and 2020 were retrieved (Table 1). [15][16][17][18][19][20][21][22][23][24][25][26] These studies covered a total of 1676 patients. Authors of those studies investigated various thresholds to discriminate MIBC from NMIBC.…”
Section: Vi-rads Score Performancementioning
confidence: 99%
“…The sensitivity ranged from 78% to 100%, specificity from 44% to 100%. [15][16][17][18][19][20][21][22][23][24] For a VI-RADS 4 threshold, sensitivity ranged from 63 to 100%, specificity from 76% to 96% (including 7 studies with 88 patients). 15,16,19,[21][22][23] Finally, for a VI-RADS 5 threshold, the sensitivity ranged from 68% to 86%, and the specificity from 95% to Figure 3.…”
Section: Vi-rads Score Performancementioning
confidence: 99%
See 1 more Smart Citation